Platinum Nanoparticles Confined Within tio2 Nanotube Matrix for Enhanced Catalytic Reduction of Azure B Dye - Singh, D (Elsevier B.V., 2023)
In this work, we report the synthesis of TiO2 nanotubes encapsulated platinum nanoparticles (PtNPs-TiO2NTs) as a highly efficient catalyst for the catalytic reduction of azure B (AZB) dye in the sodium borohydride (NaBH4) medium. The encapsulation of PtNPs (particle size ∼ 2–3 nm) inside the TiO2NTs was confirmed by HR-TEM analysis. The as-prepared PtNPs-TiO2NTs exhibit higher conversion efficiency than 99 % with a pseudo-first order rate constant of 2.6 × 10-3 s−1. Owing to the confinement effect of PtNPs inside the TiO2NTs, the synthesized catalyst shows the superior operative stability even after 8 consecutive recycles without any loss in its activity. This work opens up new avenue for the designing of confined catalyst for various industrial catalytic reactions. © 2022 Elsevier B.V.